Expression of P2 receptors in human B cells and Epstein-Barr virus-transformed lymphoblastoid cell lines - Lee, Dong Hyeon (BioMed Central, 2006)
BACKGROUND: Epstein-Barr virus (EBV) infection immortalizes primary B cells in vitro and generates lymphoblastoid cell lines (LCLs), which are used for several purposes in immunological and genetic studies. Purinergic receptors, consisting of P2X and P2Y, are activated by extracellular nucleotides in most tissues and exert various physiological effects. In B cells, especially EBV-induced LCLs, their expression and function have not been well studied. We investigated the expression of P2 receptors on primary human B cells and LCLs using the quantitative reverse transcriptase-polymerase chain reaction (RT-PCR) method for revealing the gene expression profile of the P2 receptor subtypes and their changes during transformation. RESULTS: The mRNA transcripts of most P2 receptors were detected in primary B cells; the expression of P2X(3 )and P2X(7 )receptors was the lowest of all the P2 receptors. By contrast, LCLs expressed several dominant P2 receptors – P2X(4), P2X(5), and P2Y(11 )– in amounts similar to those seen in B cells infected with EBV for 2 weeks. The amount of most P2 subtypes in LCLs or EBV-infected B cells was lower than in normal B cells. However, the amount of P2X(7 )receptor expressed in LCLs was higher. Protein expression was studied using Western blotting to confirm the mRNA findings for P2X(1), P2X(4), P2X(7), P2Y(1), and P2Y(11 )receptors. ATP increased the intracellular free Ca(2+ )concentration ([Ca(2+)](i)) by enhancing the Ca(2+ )influx in both B cells and LCLs in a dose-dependent manner. CONCLUSION: These findings describe P2 receptor expression profiles and the effects of purinergic stimuli on B cells and suggest some plasticity in the expression of the P2 receptor phenotype. This may help explain the nature and effect of P2 receptors on B cells and their role in altering the characteristics of LCLs.